2022
DOI: 10.3390/ph15010106
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Cyclic Sulfonamides with an N-Arylacetamide Group as α-Glucosidase and α-Amylase Inhibitors: Biological Evaluation and Molecular Modeling

Abstract: Diabetes mellitus (DM), a complicated metabolic disorder, is due to insensitivity to insulin function or reduction in insulin secretion, which results in postprandial hyperglycemia. α-Glucosidase inhibitors (AGIs) and α-amylase inhibitors (AAIs) block the function of digestive enzymes, which delays the carbohydrate hydrolysis process and ultimately helps to control the postprandial hyperglycemia. Diversified 2-(3-(3-methoxybenzoyl)-4-hydroxy-1,1-dioxido-2H-benzo[e][1,2]thiazin-2-yl)-N-arylacetamides were synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 87 publications
0
9
0
Order By: Relevance
“…The resulting oligosaccharides are further hydrolyzed into absorbable α- d -glucose by α-glucosidase (EC 3.2.1.20) located at the intestine’s brush boundary, leading to an increase in blood sugar level (Figure ). Thus, inhibition on either of these enzymes can be a solution to blood sugar regulation. Indeed, acarbose, miglitol and voglibose are clinically prescribed α-amylase and α-glucosidase inhibitors for the treatment of T2DM. , However, serious side effects such as diarrhea, gastrointestinal distress, and abdominal distension are often reported during the application of those medicines. , Several enzymatic studies have documented that α-amylase inhibition is one of the leading causes for gastrointestinal side effects, as it can also facilitate the transfer of undigested polysaccharides to the intestine .…”
mentioning
confidence: 99%
“…The resulting oligosaccharides are further hydrolyzed into absorbable α- d -glucose by α-glucosidase (EC 3.2.1.20) located at the intestine’s brush boundary, leading to an increase in blood sugar level (Figure ). Thus, inhibition on either of these enzymes can be a solution to blood sugar regulation. Indeed, acarbose, miglitol and voglibose are clinically prescribed α-amylase and α-glucosidase inhibitors for the treatment of T2DM. , However, serious side effects such as diarrhea, gastrointestinal distress, and abdominal distension are often reported during the application of those medicines. , Several enzymatic studies have documented that α-amylase inhibition is one of the leading causes for gastrointestinal side effects, as it can also facilitate the transfer of undigested polysaccharides to the intestine .…”
mentioning
confidence: 99%
“…In previously reported in silico studies, a number of 1,2-benzothiazine and xanthone derivatives, 8-c-ascorbyl(-)-epigallocatechin, and Voglibose also showed α-glucosidase inhibition through interaction with Asp203, Asp542, and Arg526 pocket residues of the receptor protein [ 47 , 48 , 49 , 50 ]. Additionally, reported molecular docking studies of 1, 2-benzothiazine derivative against α-amylase indicated excellent binding affinities with the residues TRP83, ASP340, ARG 204, and GLU 230 [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…The selected compound (Figure 1), 2-(3-benzoyl-4-hydroxy-1,1-dioxido-2H-benzo[e] [1,2]thiazin-2-yl)-1-(2-bromophenyl) acetamide (FA2) was synthesized by reported methodology (Scheme 1). 30 The 3-benzoyl-4-hydroxy-1,2-benzothiazine 1,1-dioxide (0.5 g, 1.66 mmoles), 2-bromo-N-(2-bromophenyl) acetamide (0.49 g, 1.67 mmoles) and K2CO3 (0.46 g, 2.33 mmoles) were mixed in dimethyl formamide (10 mL). The reaction mixture was vortex for 10 minutes at 28-30 °C, then heated at 100 °C for 120 minutes.…”
Section: Materials and Methods Chemistrymentioning
confidence: 99%